Coating Fe3O4 quantum dots with sodium alginate showing enhanced catalysis for capillary array-based rapid analysis of H2O2 in milk. (30th June 2022) - Li, Pan; Zhang, Sheng; Xu, Chenchen; Zhang, Lixiang; Liu, Qingqing; Chu, Su; Li, Shuai; Mao, Guojiang; Wang, Hua
Highlights: Fe3 O4 QDs can present higher peroxidase-like catalysis than Fe3 O4 NPs. Enhanced catalysis can be achieved for Fe3 O4 QDs if coated with sodium alginate. Fe3 O4 QDs were coated onto capillary tubes by SA with film-forming capacity. Automatic fetching of multiple samples can be expected by the capillarity power. Capillary array-based colorimetric platform enables high-throughput detection of H2 O2 . Abstract: A simple and high-throughput colorimetric analysis array has been constructed for quantifying H2 O2 in milk using Fe3 O4 quantum dots (QDs), which were coated with sodium alginate (SA) and chromogenic substrate onto the arrayed capillary tubes. It was discovered that the Fe3 O4 QDs could present larger peroxidase-like catalysis than Fe3 O4 nanoparticles (NPs). Particularly, dramatically enhanced catalysis activity could be achieved for Fe3 O4 QDs if coated with SA films. Moreover, the use of SA could protect Fe3 O4 QDs to expect the improved environmental stability. A capillary arrays-based high-throughput colorimetric platform was thereby developed for the detection of H2 O2 in milk, with levels linearly ranging from 10 to 400 μM. Importantly, the developed colorimetric platform with the capillarity power for automatic fetching of multiple samples may promise the practical applications for extensive monitoring of multiple H2 O2 samples for food safety.